Exploring Students’ Statistical Reasoning through the Statistical Reasoning Learning Environment - 'Adna, Syita Fatih; Parta, I Nengah; Anwar , Lathiful; Azhar, Farid; Darmawan, Puguh Andhia (Indonesian Journal of Mathematics Education, 2025)
This study aimed to (1) analyze students’ statistical reasoning achievement through the Midterm Exam in the Educational Research Statistics course, (2) evaluate lecturers’ adherence to Statistical Reasoning Learning Environment (SRLE) principles using the Statistics Teaching Inventory (STI), and (3) examine the relationship between students’ reasoning outcomes and SRLE implementation. Employing a descriptive quantitative-qualitative method with purposive sampling of one class, data were collected from exam results and STI responses. The findings indicate that students demonstrated strong performance in the aspects of Describing (approximately 89%), Organizing (75.8%), and interpreting data in the context of the t-test (71.6%). However, difficulties remain in the aspect of Representing Data, particularly in one-way ANOVA tasks that require Interpreting SPSS outputs, which only reached 64.4%. Meanwhile, the STI results show that lecturers’ adherence to SRLE principles falls within the moderate to high category (scale 3–5), especially in the application of contextual tasks and the use of real data, both receiving the highest score of 5. These results emphasize the need to enhance students’ skills in representing and interpreting complex data and the importance of consistent SRLE implementation to foster statistical reasoning development.